The Paradox of Education, Productivity and Career Development - Endang Sri Soesilowati (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
This study focuses on productivity and the career development of workers in Indonesia, especially those with tertiary education qualifications. Education, for some sets of workers, is a significant determinant in boosting productivity. Others confirm that their productivity is principally related to education, though less directly, because it is a signalling or screening device that is necessary to enable promotion or career development. The significance of education can be recognised by considering that workers’ ability to absorb new instructions or to understand advanced technology is determined by their education. The more advanced their education, the more responsive they will be. Individual ability to innovate and produce is much more possible for educated workers. For career development, the education level makes a significant contribution to promotion or career development for male and for female workers, but not to the same degree. In addition, the educational background controls to some extent the position and work levels of employees. However, based on some case studies in manufacturing industries, there is a scarcity of female employees holding higher-level positions, such as manager. Because of that, we cannot easily make valid comparisons or draw firm conclusions. In fact, although a woman might have an education to graduate level, she might not get a position equivalent to that of a male similarly educated. Female employees used to be a bit pessimistic about aspiring to develop their careers in terms of gaining higher job positions but, men in contrast, were more optimistic in their aspirations.